Malay cultural health belief - Sulaiman, Szariannie (2018)
This study focuses on several breast cancer patients among young Malay women in several areas in Selangor and Klang Valley. The poor and low survival rates among Malay breast cancer patients has posed many challenges not only to health practitioners but also to care givers in making sense and managing their illness experiences. In relation to this, 13 breast cancer patients between the ages of 29 and 48 years old were selected for this study. The objective of this study is to explore cultural health belief system among Malay informants. The study employed qualitative approach using participant observation and in-depth interview. The findings of this study highlight several issues related to the concepts of health and illness. It was evident in this study that Malay informants’ health belief is rooted in their culture. Malay cultural health belief system is derived from occult and holistic traditions. They strongly believed that health and illness are strongly associated with semangat, the role played by malevolent spirit, lack of kudrat and pattern of food consumption. Finally, this study holds an important implication in contributing to the existing corpus of knowledge as far as medical anthropology is concerned.